Syrian hamster as an ideal animal model for evaluation of cancer immunotherapy - Jia, Yangyang; Wang, Yanru; Dunmall, Louisa S Chard; Lemoine, Nicholas R.; Wang, Pengju; Wang, Yaohe (Frontiers in Immunology, 2023)
Cancer immunotherapy (CIT) has emerged as an exciting new pillar of cancer treatment. Although benefits have been achieved in individual patients, the overall response rate is still not satisfactory. To address this, an ideal preclinical animal model for evaluating CIT is urgently needed. Syrian hamsters present similar features to humans with regard to their anatomy, physiology, and pathology. Notably, the histological features and pathological progression of tumors and the complexity of the tumor microenvironment are equivalent to the human scenario. This article reviews the current tumor models in Syrian hamster and the latest progress in their application to development of tumor treatments including immune checkpoint inhibitors, cytokines, adoptive cell therapy, cancer vaccines, and oncolytic viruses. This progress strongly advocates Syrian hamster as an ideal animal model for development and assessment of CIT for human cancer treatments. Additionally, the challenges of the Syrian hamster as an animal model for CIT are also discussed.